PENERAPAN PENDEKATAN PEMBELAJARAN JELAJAH ALAM SEKITAR (JAS) TERHADAP PEMAHAMAN KONSEP SISWA - Afifah, Rachma; Sugianto, Sugianto; Astuti, Budi (UPEJ Unnes Physics Education Journal, 2017)
The research aims was to understand the influence of approach JAS with understanding the concept of students. This research used experimental with the form of the control grup posttest design. The research sample used was classes XI TKR 1 and XI TKR 2 SMK N 10 Semarang. Sampling was done by purposive sampling technique. This research obtained results of average cognitive value of experiment class 76,89 and control class 74,60 and affective assessment experiment class is including on very good criteria and control class including on good criteria. The analysis result of concept understanding profile of experiment class that showed highest percentage is classifying and generalize.  Percentage that gained is 93,33%. Based on that result it can be concluded that a class using JAS method have a higher average value affective value on the very good criteria.